The Relationship between Result-Based Management and Receiving the Award of the Office of the Basic Education Commission of Schools Under the Secondary Educational Service Area Office of Nonthab - Panya, Wichapon; Namawiroj, Panote (Journal of Graduate MCU KhonKaen Campus, 2025)
This quantitative research aimed to: 1) study the level of results-based management in schools under the Secondary Educational Service Area Office Nonthaburi; 2) examine the level of implementation based on the Office of the Basic Education Commission Quality Award (OBECQA) criteria; and 3) investigate the relationship between results-based management and implementation according to the OBECQA criteria. The sample consisted of 270 teachers from seven schools that received the OBECQA award in 2023. The sample size was determined using the Krejcie and Morgan table from a population of 908 teachers. The research instrument was a questionnaire with an Index of Item-Objective Congruence (IOC) ranging from 0.67 to 1.00 and a reliability coefficient of .96. Data were analyzed using percentage, mean, standard deviation, and Pearson’s Product-Moment Correlation Coefficient. The findings revealed that: 1. The overall level of results-based management in schools under the Secondary Educational Service Area Office Nonthaburi was at a high level ( = 4.19, S.D. = 0.71). The aspect with the highest mean score was performance indicator determination. 2. The overall implementation according to the Office of the Basic Education Commission Quality Award (OBECQA) criteria was at a high level ( = 4.16, S.D. = 0.67). The aspect with the highest mean score was measurement, analysis, and knowledge management. 3. Results-based management was positively correlated with implementation according to the OBECQA criteria at the .01 level of statistical significance. In particular, performance evaluation, performance agreements for goal recognition, and organizational objective setting showed strong positive relationships with OBECQA implementation. These findings indicate that results-based management is a significant factor contributing to excellence in school administration and management in accordance with the OBECQA criteria.